As incidências do ensino de Lacan na compreensão da psicose e do autismo em crianças - Vanessa Gama Pozzato (2014)
The dissertation proposes to investigate infantile psychosis and autism from the standpoint of Jacques Lacans theorization. We begin our inquiry trailing the path opened by psychiatry in its attempt to delineate the clinical profiles of both infantile psychosis and autism, establishing a separation between them, which has occurred throughout the development of this field of knowledge. Afterwards, we try to answer the same question in relation to psychoanalysis, still grounding our research in Jacques Lacans theory. We extract from his work clinical cases descriptions as well as some appointments regarding the issue in question, attempting to perceive how Lacan initially understood the functioning of psychosis, distinguishing it from neuroses, in order to properly grasp the concept of psychosis and its evolution in the course of the Lacanian teaching. Thereafter, we single out the references made by author concerning autism and infantile psychosis, which are constant in his comments on some clinical cases and in various other works. Subsequently, we approach some major concepts in Lacans body of work, without which we could not understand the arguments drawn by authors of Lacanian persuasion who present distinctions and approximations between infantile psychosis and autism. The gathering of remarks made by Jean-Claude Maleval, Angela Vorcaro, Colette Soler, Angélica Bastos, Ana Beatriz Freire, Eric Laurent, Flávia Azevedo e Alfredo Jerusalinsky, amongst others who have treated the subject at hand, brought forth the difficulties faced by each one of them. Consequently, at the end of our research we came across a conclusion that does not intend to be definitive, but rather aims to instigate the reader to reflect more profoundly on the theme of this research.